Electrostatically assembled gold nanocluster-enhanced porphyrinic metal-organic framework nanozymes for oxygen-boosted photodynamic therapy of hypoxic tumors - Ao He; Juan Zhou; Jing Zhu; Guojing Hong; Minglan Fan; Yuyan Bao; Rong Li; Manxiao Cheng; Xiang Ran (Journal of Photochemistry and Photobiology B: Biology, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

School greenspace and myopia incidence and burden in Chinese children and adolescents: The Guangzhou children and adolescents cohort study - Xiao-Qi Zhu; Yi Sun; Rong Lin; Ya-Na Luo; Jia-Xin Li; Yi-Dan Zhang; Michael S. Bloom; Matthew H.E.M. Browning; Sam SS. Lau; Shu-Jun Fan; Zhi-Qi Li; Ming-Deng Xiang; et al. (Environmental Research, 2026)

Lengthening vegetation carbon turnover time across China’s forests - Rong Ge; Xiaoli Ren; Honglin He; Guirui Yu; Li Zhang; Qian Xu; Mengyu Zhang; Shilong Piao; Kailiang Yu; Mathew Williams; Xiaobo Zhu; Shiyong Yu; et al. (Science Bulletin, 2026)

Mechanism of synergistic astringency enhancement by organic acids in model wine: Insights from organic acid-phenols-protein triadic interaction - Yan Liu; Xiang Jie Jiang; Shi qing Zhang; Qing hao Zhao; Yue fan Zhao; Wan Rong Zhao; Shi Yi Peng; Guo Rong Du; Xiao Yuan; Peng Tao Zhao; Xiao Yu Wang (Food Chemistry, 2026)

Everything is everywhere, but everywhere is different: evidence from the phylogeography of asexual bdelloid rotifer Rotaria rotatoria species complex - Lingyun Zhu; Rong Huang; Sen Feng; Fan Gao; Meng Li; Hairong Lian; Zhizhong Li; Xinfeng Cheng; Mingbo Yin; Wei Zhang; Yilong Xi; Xianling Xiang (Hydrobiologia, 2026)

Systematic investigation, expression analysis of TCP transcription factors in eggplant and functional characterization of SmTCP3 gene involved in response to drought stress - Fa-xiang Wan; Yu Zheng; Rong-rong Li; Ying-fan Zhang; Hua-ju Zheng; Ji-qing Li; Yi-min Jiang; Jia-rui Yang; Bo Qi; Jun Gao; Ya-nan Chen; Yu Pan (Genetic Resources and Crop Evolution, 2026)

Genetic diversity and population structure of four Trapa species from the Yangtze River and Amur River basins, China - Miriam Chepkwemoi Tengwer; Godfrey Kinyori Wagutu; Henry Kariuki Njeri; Wei Li; Yuan-Yuan Chen; Xiang-Rong Fan (Aquatic Botany, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

The prognostic significance of histopathological growth patterns in liver metastases undergoing surgery: a systematic review and meta-analysis - Xiang-Yu Wang; Bo Zhang; Yin-Chen Gu; Mei Yang; Bao-Rui Tao; Rong-Quan Sun; Yi-Tong Li; Zhen-Mei Chen; Sen-Feng Ying; Chen-He Yi; Yan Geng; Rui Zhang; et al. (Clinical & Experimental Metastasis, 2025)

Exploring morphological heterogeneity of circulating tumor cells: machine learning-based approach for cell identification and prognostic implications - Peng-Xiang Wang; Yu-Chen Zhong; Bin Duan; Jian-Wen Cheng; Yun-Fan Sun; Wen-Jing Zheng; Kai-Qian Zhou; Yang Xu; Hai-Xiang Peng; Wei-Xiang Jin; Hai-Min Li; Xiao-Juan Sun; et al. (Science Bulletin, 2025)

Genome-wide identification reveals a bZIP transcription factor modulating chlorophyll catabolism during leaf yellowing in harvested Chinese flowering cabbage - Ze-xiang Zeng; Yuan Rong; Zhong-qi Fan; Xin-guo Su; Lin Chen; Yan-chao Han; Hang-jun Chen; Wei Wei; Wei Shan; Jian-fei Kuang; Wang-jin Lu; Jian-ye Chen (Postharvest Biology and Technology, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Au-isolated Pt active site with enhanced C-H bond activation ability for selective oxidation of polyol to hydroxyl acid - Xuewei Ding; Ying Liao; Rong Fan; Hao Yan; Xin Zhou; Xiang Feng; Xiaobo Chen; Hui Zhao; Yibin Liu; Chaohe Yang (Chemical Engineering Journal, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Associations between volatile organic compounds exposure and multiple oxidative damage biomarkers: Method development, human exposure, and application for e-waste pollution prediction - Jia-Rong Wang; Hong-Xuan Kuang; Ye Liu; Xin-Yi Li; Tian-Hong Chen; Xiao-Hui Zhu; Rui-Fang Fan; Ming-Deng Xiang; Yun-Jiang Yu (Science of The Total Environment, 2024)

A compound heterozygous mutation of ERCC8 is responsible for a family with Cockayne syndrome - Meng-Wei Liu; Cheng-Feng Hu; Jie-Yuan Jin; Rong Xiang; Liang-liang Fan; Ya-Li Li; Lei Zhu (Molecular Biology Reports, 2024)

SeismicTransformer: An attention-based deep learning method for the simulation of seismic wavefields - Yanjin Xiang; Zhiliang Wang; Ziang Song; Rong Huang; Guojie Song; Fan Min (Computers & Geosciences, 2024)

Novel insights into dimethylsulfoniopropionate cleavage by deep subseafloor fungi - Xuan Liu; Xin-Ran Wang; Fan Zhou; Ya-Rong Xue; Xiang-Yang Yu; Chang-Hong Liu (Science of The Total Environment, 2024)

Drought reduces peanut yield indirectly through regulating soil nematode community in a manipulative field experiment in central China - Cancan Zhao; Rong Fan; Xiaolin Li; Like Fan; Liwei Zhang; Xinyu Yan; Xiang Zhao; Yuan Miao; Yanfeng Sun; Yuanhu Shao; Guoyong Li; Shenglei Fu (Applied Soil Ecology, 2024)

The phylogenetic analysis of two invasive Trapa species in the United States revealed by chloroplast genomes and morphological traits - Xiang-Rong Fan; Nancy Rybicki; Lynde L. Dodd; Jie Min; Wei Li; Xiu-Ling Li; Godfrey Kinyori Wagutu; Yuan-Yuan Chen (Biological Invasions, 2024)

Diisoprenyl-cyclohexene-type meroterpenoids from a mangrove endophytic fungus Aspergillus sp. GXNU-Y65 and their anti-nonalcoholic steatohepatitis activity in AML12 cells - Feng Qin; Li Luo; Yu-Chen Liu; Xiang-Long Bo; Fu-Rong Wu; Fan-Fan Wang; Mei-Jing Tan; You-Quan Wei; Xiao-Bing Dou; Cai Yi Wang; Xi-Shan Huang; Heng-Shan Wang (Phytochemistry, 2024)

Dorsal root ganglia P2X4 and P2X7 receptors contribute to diabetes-induced hyperalgesia and the downregulation of electroacupuncture on P2X4 and P2X7 - Qun-qi Hu; Xiao-fen He; Yi-qi Ma; Li-qian Ma; Si-ying Qu; Han-zhi Wang; Yu-rong Kang; Lu-hang Chen; Xiang Li; Bo-yu Liu; Xiao-mei Shao; Jun-fan Fang; et al. (Purinergic Signalling, 2023)

A chitin synthase mutation confers widespread resistance to buprofezin, a chitin synthesis inhibitor, in the brown planthopper, Nilaparvata lugens - Bin Zeng; Fu-Rong Chen; Ya-Ting Liu; Di Guo; Yi-Jie Zhang; Ze-Rui Feng; Li-Xiang Wang; John Vontas; Shun-Fan Wu; Kun Yan Zhu; Cong-Fen Gao (Journal of Pest Science, 2023)

The association of air pollutants with hospital outpatient visits for child and adolescence psychiatry in Shenzhen, China - Dong Fang; Wang Bing; Han Yao-hui; Jing Chun-xia; Zhang Ying; Liu Xing-li; Tian Hua-wei; Xiang Ying-jun; Liao Wan-wei; Li Xiu-juan; Fan Dong-yong; Yang Wei-ting; et al. (Environmental Research, 2023)

Astragalus Polysaccharides Reduce High-glucose-induced Rat Aortic Endothelial Cell Senescence and Inflammasome Activation by Modulating the Mitochondrial Na+/Ca2+ Exchanger - Xin-Yu Miao; Xiao-Xiao Zhu; Zhao-Yan Gu; Bo Fu; Shao-Yuan Cui; Yuan Zu; Ling-Jun Rong; Fan Hu; Xiang-Mei Chen; Yan-Ping Gong; Chun-Lin Li (Cell Biochemistry and Biophysics, 2022)

Markers and Genetic Mechanisms of Primary and Epigenetic Oxidation of an Aeolian Depositional System of the Luohandong Formation, Ordos Basin - Yao Xiang; Yangquan Jiao; Liqun Wu; Hui Rong; Fan Zhang (Journal of Earth Science, 2022)

Infestation and distribution of mites on the Yunnan red-backed vole (Eothenomys miletus) in Yunnan Province of southwest China between 2001 and 2015 - Rong Xiang; Xian-Guo Guo; Tian-Guang Ren; Cheng-Fu Zhao; Rong Fan; Zhi-Wei Zhang; Ke-Yu Mao; Pei-Ying Peng; Xiao-Bin Huang; Ti-Jun Qian (Biologia, 2022)

Infestation and distribution of gamasid mites on Himalayan field rat (Rattus nitidus) in Yunnan Province of Southwest China - Rong Xiang; Xian-Guo Guo; Cheng-Fu Zhao; Rong Fan; Ke-Yu Mao; Zhi-Wei Zhang; Xiao-Bin Huang (Biologia, 2021)

lncRNA H19 sponging miR-93 to regulate inflammation in retinal epithelial cells under hyperglycemia via XBP1s - Rong Luo; Fan Xiao; Pei Wang; Yu-Xiang Hu (Inflammation Research, 2020)

Preparation and In vitro Evaluation of FDM 3D-Printed Ellipsoid-Shaped Gastric Floating Tablets with Low Infill Percentages - Di Chen; Xiang-Yu Xu; Rui Li; Gen-Ao Zang; Yue Zhang; Ming-Rui Wang; Meng-Fei Xiong; Jia-Rui Xu; Ting Wang; Hui Fu; Qin Hu; Bin Wu; et al. (AAPS PharmSciTech, 2020)

Effects of nutrient addition on foliar phosphorus fractions and their resorption in different-aged leaves of Chinese fir in subtropical China - Fang-Chao Wang; Xiang-Min Fang; G. Geoff Wang; Rong Mao; Xiao-Fan Lin; Huimin Wang; Fu-Sheng Chen (Plant and Soil, 2019)

Non-monotonic Relaxation and Memory Effect of Rock Salt - Yi He; Deyi Jiang; Jie Chen; Rong Liu; Jinyang Fan; Xiang Jiang (Rock Mechanics and Rock Engineering, 2019)

Selective and novel cyclin-dependent kinases 4 inhibitor: synthesis and biological evaluation - Qingxiang Guo; Yongtao Li; Chao Zhang; Zhi Huang; Xin Wang; Yongwei Nie; Yao Li; Yanhua Liu; Shengyong Yang; Rong Xiang; Yan Fan (Medicinal Chemistry Research, 2018)

The LXR ligand GW3965 inhibits Newcastle disease virus infection by affecting cholesterol homeostasis - Xiang-xiang Sheng; Ying-jie Sun; Yuan Zhan; Yu-rong Qu; Hua-xia Wang; Miao Luo; Ying Liao; Xu-sheng Qiu; Chan Ding; Hong-jie Fan; Xiang Mao (Archives of Virology, 2016)

Flavobacterium shanxiense sp. nov., Isolated from Soil - Fan Yang; Hong-ming Liu; Rong Zhang; Ding-bin Chen; Xiang Wang; Xin Yan; Qing Hong; Shun-peng Li (Current Microbiology, 2015)

An overview of studies on psychological well-being in children born following assisted reproductive technologies - Qi-tao Zhan; Pei-pei Pan; Xiang-rong Xu; Hang-ying Lou; Yi-yun Lou; Fan Jin (Journal of Zhejiang University-SCIENCE B, 2013)

Persistence and intergenerational transmission of differentially expressed genes in the testes of intracytoplasmic sperm injection conceived mice - Li-ya Wang; Ning Wang; Fang Le; Lei Li; Le-jun Li; Xiao-zhen Liu; Ying-ming Zheng; Hang-ying Lou; Xiang-rong Xu; Xiao-ming Zhu; Yi-min Zhu; He-feng Huang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Comparative analysis of water stress-responsive transcriptomes in drought-susceptible and -tolerant wheat (Triticum aestivum L.) - Yong Chun Li; Fan Rong Meng; Chun Yan Zhang; Ning Zhang; Ming Shan Sun; Jiang Ping Ren; Hong Bin Niu; Xiang Wang; Jun Yin (Journal of Plant Biology, 2012)

Normal epigenetic inheritance in mice conceived by in vitro fertilization and embryo transfer - Lei Li; Fang Le; Li-ya Wang; Xiang-rong Xu; Hang-ying Lou; Ying-ming Zheng; Jiang-zhong Sheng; He-feng Huang; Fan Jin (Journal of Zhejiang University-SCIENCE B, 2011)

Anticancer Drug-Loaded Nanospheres Based on Biodegradable Amphiphilic ε-Caprolactone and Carbonate Copolymers - Guo-Ping Yan; Rong-Feng Zong; Liang Li; Ting Fu; Fan Liu; Xiang-Hua Yu (Pharmaceutical Research, 2010)

Systematic biotic responses to palaeoenvironmental change in the Late Pleistocene southern South China Sea: a preliminary study - Muhong Chen; Qianyu Li; Lanlan Zhang; Fan Zheng; Jun Lu; Rong Xiang; Lili Zhang; Wen Yan; Zhong Chen; Shangbin Xiao (Journal of Quaternary Science, 2008)
Oxygen and carbon isotopes from the planktonic foraminifer Globigerinoides sacculifer , trace element contents, calcium carbonate, biogenic silica, grain size, and abundances of diatoms, radiolarians and foraminifera in a deep‐sea core from the southwestern South China Sea were analysed to investigate the response of various marine ecological communities to environmental changes over the last 200 ka. The synthesised results show that the quality of the palaeoecological environment for biological growth is primarily affected by nutrient supply and terrigenous disturbance. Ba and P are important nutrient elements for the growth of diatoms, radiolarians and planktonic foraminifera. Together with dissolved silica and calcium carbonate in sea water, these elements may control microbiotic development. However, variations in Fe content appear to affect diatom and radiolarian abundance. Optimal biotic growth occurs when nutrients are abundant and when there is minimal terrigenous disturbance. Biotic growth decreases when sea water is highly oligotrophic and terrigenous input is high. Maximum biological growth occurred in the mid Holocene, but deteriorated soon afterwards owing to increased terrigenous input, causing a decrease of biological abundance and productivity in the late Holocene. The results also indicate how the Toba volcanic eruption ca. 74 ka ago contributed to changing the ecological environment in the southern South China Sea. Copyright © 2008 John Wiley & Sons, Ltd.

BRD2 is one of BRD7-interacting proteins and its over-expression could initiate apoptosis - Ming Zhou; Xiao-Jie Xu; Hou-De Zhou; Hua-Ying Liu; Jia-Jin He; Xiao-Ling Li; Cong Peng; Wei Xiong; Song-Qing Fan; Jian-Hong Lu; Jue Ouyang; Shou-Rong Shen; et al. (Molecular and Cellular Biochemistry, 2006)